Pembelajaran IPAS yang Bermakna: Peran Model Pembelajaran Make a Match dalam Meningkatkan Keaktifan Siswa di Madrasah Ibtidaiyah - Mufidah, Frida Lailis; Martanti, Fitria; Farda, Ummu Jauharin (TARBAWIYAT, 2025)
This research aims to enhance the activeness and quality of the IPAS learning process by applying the Make a Match learning model to grade V students at MI Miftahul Huda Watuaji 02. This study uses the Classroom Action Research (PTK) approach, which is carried out in two cycles, with the research subjects of all grade V students. The study's results showed a significant improvement in the quality of the learning process and student learning activities. The average percentage of teachers' teaching activities increased from 71.55% in the first cycle with the fair category to 94.11% in the second cycle with the good category. Student learning activity has also increased, as shown by an average percentage increase from 67.72% in the first cycle to 82.69% in the second cycle, in the good category. The application of the Make a Match model can create an active, interactive, and fun learning atmosphere, thereby encouraging students to be more confident, dare to speak their minds, and be optimally involved in the learning process. Thus, the Make a Match model is effectively used as an alternative to IPAS learning strategies to improve the activeness and quality of the learning process of elementary school students.